The Influence of Using Moodle-Based Learning Media on Informatics Subjects: Pengaruh Penggunaan Media Pembelajaran Berbasis Moodle pada Mata Pelajaran Informatika - Dwi Krisna Mukti; Juan Mikhael Silaban; Raja Sakti Arief D (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to promote a more effective learning process through the use of the Moodle e-learning platform. Moodle was chosen because it can overcome the limitations of time and place in the teaching and learning process, as well as facilitate students in evaluating various completed learning activities. In addition, the platform offers features that support the implementation of online learning, such as delivering materials, submitting assignments, and providing structured academic information. This research employed a quantitative method based on observations conducted at SMA Dharma Pancasila Medan. The results showed that using Moodle as a learning medium significantly supported the students' learning process, particularly in a school that previously lacked an organized digital learning system. The implementation of Moodle has proven effective in addressing learning issues such as limited face-to-face interaction and challenges in distributing materials. Thus, the use of Moodle in teaching and learning activities has the potential to improve overall learning effectiveness. The findings also indicate that integrating technology into education, when done appropriately, can offer innovative solutions to various challenges in the educational landscape, especially in today's digital era.